(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Animal husbandry plays a significant role in the world economy. The advancement in new technologies such as the Internet of Things (IoT) and Cloud Computing plays a vital role in governing the health of the livestock, tracking their live location and also smart feeding the cattle. The targeted survey was designed mainly to focus on precision livestock farming (PLF) techniques which helps to improve animal health, welfare, and farm efficiency. The evidence of the interest in, and significant presence of, PLF tools for the individual monitoring of livestock are provided in the survey. Here, in this study, we have discussed about the recent and updated research on the various livestock monitoring and management systems.